Hemitruncus with ventricular septal defect in a 6-year-old child - Sachin Talwar; Ajay Meena; Sivasubramanian Ramakrishnan; Shiv Kumar Choudhary; Balram Airan (Wolters Kluwer Medknow Publications, 2013)
We report a 6-year-old girl with anomalous origin of the right pulmonary artery from the aorta associated with a large ventricular septal defect. The challenges in the assessment of operability and issues in the surgical management are discussed.